A lethal juvenile mouse model for the evaluation of antiviral reagents against coxsackievirus A4 - Qin Su; Xiao Chen; Zhihui Zheng; Hailin Wei; Jiaxue Zhou; Libing Zhang; Ali Muhammad; Yin Wang; Xiang Chen; Pinghu Zhang (iScience)
Summary: Coxsackievirus A4 (CVA4) as a pathogen causing severe herpangina has become global outbreak epidemics during the past 5 years. However, there is currently no effective vaccines and drugs available. Here, one mouse-adapted CVA4 virus (YZ08) was cultivated by repeatedly cross-passaging between human RD cells and 11-day-old juvenile mice. Our results revealed the YZ08 virus was highly lethal to 13-day-old juvenile mice. Virus titer assay indicated that the YZ08 virus effectively replicated in juvenile mice. This model was successfully used to evaluate the therapeutic efficacy of herb medicine, anti-CVA4 rabbit sera, and antiviral drugs. Our results indicated that all tested reagents effectively provided protection for CVA4 virus infection by prolonging survival time, promoting survival, and preventing weight loss. Collectively, we successfully established a juvenile mouse model of CVA4 virus, which was a powerful tool for investigating the pathogenesis of CVA4 or evaluating the efficacy of antiviral reagents or vaccines.